Eigenvalues of the Mixture Mass Flow Model - Pokhrel, Puskar Raj; Budhathoki, Tek Bahadur (Journal of Nepal Mathematical Society, 2025)
Landslides, debris flows, and tsunamis are major geophysical mass transfer dynamics that frequently occur in mountainous regions, valleys, and lower plains. This causes severe destruction of human lives, infrastructures, and the environment. Understanding and predicting their behavior requires reliable modeling techniques capable of capturing the full dynamics of flow evolution, run-out distance, deposition characteristics, and impact forces from initiation to final deposition. Here, we employ the mixture mass flow model developed by Pokhrel et al., to derive the characteristic equations and computing the corresponding Eigenvalues. These Eigenvalues are then used to determine the Froude number and analyze its implications in flow regimes. The resulting analysis highlights the relationship between characteristic speeds, numerical stability, and the physical behaviour of mixture mass flows. The findings enhance our theoretical understanding of mixture mass flow dynamics and contribute to practical approaches for natural hazard mitigation.